Cyclical Pattern of Structural Changes in Entrepreneurship - NIKITENKO, Genadiy; NAZARENKO, Anton; ZAPOROZHETS, Dmitriy; SERGIENKO, Ekaterina; BAYDAKOV, Alexander (Journal of Advanced Research in Law and Economics, 2016)
The article describes the theoretical and methodological approaches to the study of cyclic patterns of development of systems as an example of the service sector, depending on the stage of the life cycle in the context of the evolution of entrepreneurial ideas. The possibility of using of sufficiently universal methods of efficiency forecasting of business ideas implementing with the cycles of services development was explained. The analysis of the well-known economic cycles in the time of action was carried out from the perspective of the socio-economic systems fractal. On the base of analysis of statistical data on the development of communication systems structural changes in this sphere of business in accordance with the cycles were revealed. A matching of the dynamics of agrarian business development ‘cycle length conditions’ was conducted.
Keywords: cycle; entrepreneurial business; economic cycle; sphere of communication services; agrarian